2004
DOI: 10.1159/000078809
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Germ Cell Tumor after Bilateral Orchidopexy in Persistent Müllerian Duct Syndrome with Transverse Testicular Ectopia

Abstract: The persistent müllerian duct syndrome is characterized by the retention of müllerian derivatives (fallopian tubes, uterus) in patients otherwise normally virilized, usually with cryptorchidism or an inguinal hernia. Very rarely, this syndrome is associated with transverse testicular ectopia , which designates the condition when both testes descend through the same inguinal canal into the same scrotal sac. We report on a patient with both conditions, who had T1N2M0 scrotal mixed germ cell tumor of the testis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…Manassero et al [2004] describe a patient with PMDS and transverse testicular ectopia with the presence of a mixed germ cell tumor (teratoma and embryonal carcinoma) in a testis in the scrotal position after orchidopexy at the age of 5 years, suggesting that orchidopexy early in life does not decrease the risk of malignancy in this patient group. Therefore, it has been suggested that orchidectomy should be performed [Berkmen, 1997].…”
Section: Discussionmentioning
confidence: 93%
“…Manassero et al [2004] describe a patient with PMDS and transverse testicular ectopia with the presence of a mixed germ cell tumor (teratoma and embryonal carcinoma) in a testis in the scrotal position after orchidopexy at the age of 5 years, suggesting that orchidopexy early in life does not decrease the risk of malignancy in this patient group. Therefore, it has been suggested that orchidectomy should be performed [Berkmen, 1997].…”
Section: Discussionmentioning
confidence: 93%
“…Most tumours occur after puberty, therefore long-term follow-up should be mandatory for patients with PMDS [ 20,22,24 ] . The testis should be palpated and examined for any inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…Our own perusal of the literature yields a much higher figure: 33% of PMDS patients 18 years and older experienced some form of unilateral or bilateral malignant testicular degeneration. Seminomas are the most frequent, but choriocarcinomas [Giri et al, 2004;Aboutorabi et al, 2005], mixed germ cell tumors [Eastham et al, 1992;Manassero et al, 2004;Jaka and Shankar, 2007;Mohapatra and Subramanya, 2016], embryonal cell carcinoma [Melman et al, 1981;Carré-Eusèbe et al, 1992;Barad et al, 2016], gonadoblastomas [Morillo-Cucci and German, 1971], or yolk sac tumor [Snow et al, 1985] have also been described. In our own cohort, we encountered 3 testicular tumors (H069 and H050) [Carré-Eusèbe et al, 1992] and H009, all adults with AMH mutations (online suppl.…”
Section: Malignant Degenerationmentioning
confidence: 99%